IF NOT THE NATION- A NATIONAL MINIMUM WAGE OBJECTIVE - Madhumitha, D S (PEOPLE: International Journal of Social Sciences, 2019)
India is a vast secular nation with many cultures, religions, practices as well as differences, deficiencies. It is a developing nation with its socio-economic status in paradigm. The minimum wage purposes to achieve a floor on this, It worked well until the employers found the loophole of fixing the minimum wage to be the maximum, where the workers suffered with India’s developing economic standards and global market, where value of rupees fell. Struggles and toil of workers wasn’t compensated on equal grounds throughout the nation. It differed from state to state based on their economic socio standards, a worker in Karnataka would get a different minimum wage from that of Tamil Nadu. Which is why a proposal of National Minimum wage becomes the need of the hour, everywhere the worker moves, settles or works, there is a bare necessity on the employer to follow that floor. If the nation doesn’t improve to the dynamic change of the world and its trade for protection of labour, then who would? This paper focuses on why national minimum wage is the need of the hour in comparison with a sovereign which has already a National Minimum wage and how it is effectively functioning regardless of division of power between the states and centre.